Analize in problemi prostorskega razvoja za planiranje omrežij družbene in gospodarske infrastrukture na ravni države - Gulič, Peter (Urbani izziv, 2000)
Transport networks are the most important programmes of the European Union, more precisely, the network of fast railroad and the reorganisation of air traffic. In the North european area we are thus witness to intensive planning, design and postioning corner stones, that connect raletions of mobility between expansive territorial basins and international destinations and international destinations, as well as directing transport between global economies. These starting points are the basis for analysing defined needs in directing strategic spatial development in Slovenia and understanding spatial development problems in establishing priorities.
Keywords: Europe; European Union; Evropa; Evropska unija; infrastructure; infrastruktura; promet; prostorski razvoj; prostorsko planiranje; Slovenia; Slovenija; spatial planning